Employee Voice and its Relation to the Morale of Employees in the IT Sector in South India - Muhammed, Shahab; Soumyaja, Devi (Ushus Journal of Business Management, 2021)
The study was undertaken to understand the influence of employee voice (the degree of an employee‘s say and influence in workplace decisions) on employee morale (job satisfaction, outlook, and feelings of well- being) in the IT sector. A survey was carried out among a sample of 90 IT employees with less than ten years of experience. A standardised questionnaire was used to carry out the survey. The study results indicate that employee voice has a positive influence on employee morale. Statistical analysis also indicates that there is a gender difference with respect to employee voice. The study aims to encourage management to promote a culture of increased opportunities for employee voice in a way that would, in turn, help in improving employee morale.